A Study on Academic Achievement, Perception of School Climate, And Social Support among Higher Secondary Students - Mousumi Haldar; Dr. Yashpal Singh (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This study investigates three critical dimensions of student development: academic achievement, perception of school climate, and the nature of social support among higher secondary students. The research was conducted with a sample of students from diverse educational institutions, incorporating variables such as gender, socio-economic status, and school type. The primary objectives were to assess the level of academic achievement, examine students’ perceptions of school climate, and understand the nature and extent of social support they receive from various sources including peers, teachers, and family. A descriptive survey method was employed, and standardized tools were used to measure each construct. The findings revealed that academic achievement levels varied significantly across demographic categories, with students from higher socio-economic backgrounds and private schools tending to perform better. Students’ perceptions of school climate were found to correlate with academic outcomes; those who perceived their school environment as supportive and inclusive generally achieved higher academically. Moreover, the nature and extent of social support also showed significant variation, with female students reporting higher levels of emotional and academic support. The study emphasizes the need for schools to cultivate a healthy climate that fosters mutual respect, academic encouragement, and emotional safety. Strengthening social support systems—both within school and at home—can enhance students’ academic trajectories. These findings have important implications for educators, school administrators, and policymakers aiming to foster holistic student development.